Disentangling Pay and Productivity in a Corporatist Economy: The Case of Germany - Jr. Scott M. Fuess; Meghan Millea (Institute for the Study of Labor (IZA), 2002)
Conventional theory predicts that productivity gains lead to pay hikes. Pay increases, however, can influence labor productivity. But what about in a corporatist economy? Focusing on Germany, we use an innovative technique developed by Geweke to disentangle the relationship between pay and productivity.
Keywords: J41; J30; J50; C22; 330; labor contracts; efficiency wages; corporatism; Lohn; Produktivität; Tarifpolitik; Effizienzlohn; Korporatismus; Schätzung; Deutschland